PEMAHAMAN KONSEP MATERI KEGIATAN EKONOMI MELALUI MODEL READ, ANSWER, DISCUSS, EXPLAIN, CREATE DI SEKOLAH DASAR - As'ary, Mohamad Yasin; Robandi, Babang (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
Understanding the concept of economic activities is very important for students to have since elementary school because it is the foundation so that later when they enter society, students can understand how the economic system works both at the micro and macro level. In the era of globalization and industrial revolution 4.0 where the economy is moving very dynamically, we are required to understand how the economy works so that we can adapt. The less innovative learning methods used in learning economic activity material make learning less meaningful and understanding of the concept of economic activity becomes low. This research is a descriptive qualitative study to look more deeply at how students understand the concept of economic activity material. The subjects in this research were class IV students of one of the Islamic-based private elementary schools in Bandung City for the 2022/2023 academic year. The research results show that understanding of concepts in economic activity material for interpreting, summarizing, concluding and explaining indicators is in the high category. Meanwhile, the indicators of exemplifying, classifying and comparing are in the very high category. These results were obtained after the teacher carried out learning according to the steps in the Read, Answer, Discuss, Explain and Create learning model.